Analisis Fatwa DSN-MUI No. 137/DSN-MUI/IX/2020 tentang Sukuk dalam Perspektif Fiqih Muamalah - Ilmiyah, Izzatul; Muiz, Abdul (Journal of Islamic Finance and Syariah Banking, 2023)
Sukuk are sharia securities (sharia securities) in the form of certificates or proof of ownership that have the same value and represent ownership of assets in the form of projects or investment activities after receipt of sukuk funds. The existence of sukuk in the modern era cannot be separated from the needs of companies or institutions that require capital. The legal basis for sukuk must be clear in order to avoid investments that are prohibited in Islam. Therefore, the permissibility of sukuk is contained in fatwa No. 137/DSN-MUI/IX/2020 concerning sukuk. The fatwa becomes the guidelines and rules for the provisions of Sukuk. The researcher uses the descriptive qualitative method, which is to describe the permissibility as well as the provisions and limitations related to Sukuk. The purpose of this research is to analyze the fatwa of DSN-MUI Number 137/DSN-MUI/IX/2020 according to fiqh rules. The results showed that fatwa No.137/DSN-MUI/IX/2020 was issued with the consideration that sukuk investment requires guidelines, provisions, and limitations in carrying out its activities.